2015
DOI: 10.1017/s1431927615000161
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tributyltin Chloride on Developing Mouse Oocytes and Preimplantation Embryos

Abstract: Tributyltin, an organotin, is ubiquitous in estuaries and freshwater systems. Previous reports suggest that tributyltin is an endocrine disruptor in many wildlife species and it inhibits aromatase in mammalian placental and granulosa-like tumor cell lines. However, no evidence showing the effects of tributyltin on oocytes or preimplantation embryonic developmental competence exists. Therefore, we investigated the role of tributyltin chloride (TBTCl) in the development of female oocytes and preimplantation embr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
(60 reference statements)
2
0
0
Order By: Relevance
“…Studies also indicate that ROS plays a crucial role in inducing apoptosis. Additionally, studies indicate Tributyltin chloride can cause oxidative damage by increasing the gene expression level of Sod1 , Cat , and Gpx . As expected in our research, ROS generation was evaluated and the level was increased significantly after TBTO exposure.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Studies also indicate that ROS plays a crucial role in inducing apoptosis. Additionally, studies indicate Tributyltin chloride can cause oxidative damage by increasing the gene expression level of Sod1 , Cat , and Gpx . As expected in our research, ROS generation was evaluated and the level was increased significantly after TBTO exposure.…”
Section: Discussionsupporting
confidence: 88%
“…Additionally, studies indicate Tributyltin chloride can cause oxidative damage by increasing the gene expression level of Sod1, Cat, and Gpx. 16,43 As expected in our research, ROS generation was evaluated and the level was increased significantly after TBTO exposure. Also, we found that TBTO could induce apoptosis.…”
Section: Discussionsupporting
confidence: 73%